Environmental Co-benefits and Stacking in Environmental Markets - Lankoski, Jussi (OECD Food, Agriculture and Fisheries Papers, 2015)
This paper investigates farmers' incentives to participate voluntarily in carbon offset markets when environmental credit stacking is allowed, that is, farmers can stack water quality credits with carbon credits. The implications of stacking on additionality of environmental services in interlinked markets, market participation rates, and market equilibrium prices are analysed by developing a conceptual framework of environmental credit stacking, which is applied with data estimates for the US Corn Belt. Analysis shows that credit stacking increases farmers' participation in carbon offset markets, and that such increased participation provides additionality in environmental service provision. It is further shown that ecosystem markets are interlinked so that credit price changes in one market will shift credit supply in another market, thus affecting equilibrium prices.